Islet-1 May Function as an Assistant Factor for Histone Acetylation and Regulation of Cardiac Development-Related Transcription Factor Mef2c Expression - Yu, Zhongsu (Public Library of Science, 2013)
OBJECTIVE: Islet-1 is an important transcription factor for cardiac development through mediating extensive interactions between DNA and proteins. The present study was to investigate the role of Islet-1 in regulating the expression of cardiac development-related transcription factors and mechanism. METHODS AND RESULTS: The expression of Islet-1 and histone acetylases (HATs) subtype p300 was determined in newborn mouse hearts and mouse embryonic hearts at different development stages using Western blot. The expression of Islet-1 and cardiac development-related transcription factors Mef2c, GATA4 and Tbx5 as well as histone H3 acetylation level were determined in cardiac progenitor cells with and without transfection of Islet-1 interference RNA (RNAi) in lentivirus using PCR and Western blot. Islet-1 peak expression occurred on day E14.5 in mouse embryonic heart, and was present in the promoter regions of Mef2c, GATA4 and Tbx5 that were precipitated with p300 antibody. When Islet-1 was inhibited with specific RNAi in cardiac progenitor cells, the expression of Mef2c and Tbx5, but not GATA4, was significantly suppressed along with selective reduction in histone H3 acetylation in the promoter region of Mef2c, but not GATA4 and Tbx5. The level of Mef2c DNA, not GATA4 and Tbx5, in the complex associated with p300 was significantly decreased in the cells with Islet-1 knockdown. CONCLUSIONS: These data suggested that Islet-1 might function as an assistant factor that was involved in the regulation of histone acetylation and Mef2c expression via assisting p300 on specifically targeting the promoter of Mef2c.